Adjustment problems and coping strategies of Korean missionaries - Jung, Yong-Hwan (2007)
To make an inquiry into the adjustment status of Korean missionaries in the Philippines and how they can be helped to adjust better with their work through therapeutic intervention strategies was the main objective of this study. The descriptive or status analysis research design was used as it attempts to establish the mode of behavior of the respondents which consists of 55 Korean Protestant missionaries undergoing cross-cultural work in the Philippines. The questionnaire used was adapted from the Psychology of Missionary Adjustment book by Marge Jones and Grant Jones. Prayer was often their coping mechanism. The adjustment problems and coping mechanisms which emerged from the results of the questionnaire served as basis for intervention strategies.